Genetic Algorithm Based Design and Experimental Characterization of a Highly Thermostable Metalloprotein. - Bozkurt, Esra; Perez, Marta A. S.; Hovius, Ruud; Browning, Nicholas J.; Rothlisberger, Ursula (Journal of the American Chemical Society, 2018)
The development of thermostable and solvent-tolerant metalloproteins is a long-sought goal for many applications in synthetic biology and biotechnology. In this work, we were able to engineer a highly thermostable and organic solvent-stable metallo variant of the B1 domain of protein G (GB1) with a tetrahedral zinc binding site reminiscent of the one of thermolysin. Promising candidates were designed computationally by applying a protocol based on classical and first-principles molecular dynamics simulations in combination with genetic algorithm optimization. The most promising of the computationally predicted mutants was expressed and structurally characterized and yielded a highly thermostable protein. The experimental results thus confirm the predictive power of the applied computational protein engineering approach for the de novo design of highly stable metalloproteins.